First record of the epibiont diatom Pseudohimantidium pacificum and other symbiotic associations in the Gulf of California - Gárate-Lizárraga, Ismael; Muñetón-Gómez, María del Socorro (Instituto de Ecología, A.C., 2009)
In Mexico there is little information about the symbiotic associations among diatoms on other marine microalgae and particularly, ciliates and marine planktonic crustaceans. For that reason, we report the first record of the epizoic symbiosis between the copepod Farranula gibbula and the diatom Pseudohimantidium pacificum as well as other microalgae associations with marine ciliates in Bahía de La Paz. Biological samples were collected using a 20-μm mesh plankton net in six sampling sites in Bahía de La Paz. Sixty-two male copepods of F. gibbula were found. From these, 27 specimens showed a bouquet composed of the diatom P. pacificum on its carapace. Average abundance values of P. pacificum for each sampling station ranged from 16 to 82 diatoms per copepod. Pennate diatoms were observed as epibionts on copepods belonging to the genus Acartia. In addition, other symbiotic relationships among ciliates, microalgae and cianobacteria were also encountered, outstanding the following ones: Chaetoceros coarctatum-Vorticella oceanica, Leptocylindrus mediterraneus-Solenicola setigera. The association between the diatom Fragilariopsis doliolus and the silicoflagellate Dictyocha pentagona with a Vorticella-like ciliate is reported for the first time.